2020
DOI: 10.4314/ahs.v20i3.43
|View full text |Cite
|
Sign up to set email alerts
|

Association of apoE gene polymorphisms with lipid metabolism in renal diseases

Abstract: Background and Objectives: Apolipoprotein E (apoE) plays a central role in the metabolism and homeostasis of lipids. ApoE gene encodes three major isoforms: ε2, ε3 and ε4 forming six phenotypes: Ε2Ε2, Ε2Ε3, Ε2Ε4, Ε3Ε3, Ε3Ε3 and Ε4Ε4 . Disorders of the lipid metabolism and the homeostasis are frequently coexist in renal diseases. The association be- tween gene polymorphisms of apoE and lipid metabolism were not consistent. This meta-analysis was performed to assess the association between gene polymorphisms of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Other studies revealed that APOE polymorphisms were associated with serum lipid levels in healthy controls but not in T2D patients (33,34). A meta-analysis of 16 studies revealed an association of APOE polymorphisms with the levels of TC, TG, HDL-C, and LDL-C (35). However, the inconsistent results may be attributed to the differences in the included populations, the sample sizes, genotyping methods, and other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies revealed that APOE polymorphisms were associated with serum lipid levels in healthy controls but not in T2D patients (33,34). A meta-analysis of 16 studies revealed an association of APOE polymorphisms with the levels of TC, TG, HDL-C, and LDL-C (35). However, the inconsistent results may be attributed to the differences in the included populations, the sample sizes, genotyping methods, and other risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The apolipoprotein E (Apo E) gene is located in the 2 band of the 13 region on the long arm of human chromosome 19, containing 4 exons and 3 introns (19q13.2). Apo E is a polymorphic protein synthesized mainly by the liver that influences lipid metabolism by binding to chylomicron and LDL receptors to mediate the clearance of very low density lipoproteins in serum ( Zhou et al, 2020 ). The genetic variation of Apo E is consistently associated with increased liver fat content ( Nascimento et al, 2020 ).…”
Section: Major Genetic Predisposition In Mafldmentioning
confidence: 99%
“…While Ghanain rsearchers 41 write for us on “adherence to drug therapy among hypertensive patients attending two district hospitals,” Chinese workers 42 describe the “association of apoE gene polymorphisms with lipid metabolism in renal diseases.”…”
Section: Now To Diabetes Mellitusmentioning
confidence: 99%